The Effectiveness of Psychotherapeutic Education Program in Improving Social Skills in Schizophrenia Patients - Kmichou, Halima; Klaina, Mekki; Ziani, Aicha (Darul Yasin Al Sys, 2025)
This study was conducted in response to the scarcity of Arabic research on psychotherapeutic interventions for schizophrenia compared to pharmacological treatments, which are more prevalent in Western societies. It thus represents a significant scientific contribution to this field. The study aims to enhance the social skills of individuals with schizophrenia and facilitate their reintegration into society through the implementation of a therapeutic program at Ibn Al-Hassan Psychiatric Hospital in Fez. A clinical case study approach was adopted, with a sample comprising three male patients diagnosed with schizophrenia. Data collection tools included clinical observation, medical history analysis, clinical interviews, and pre- and post-assessments using a social skills scale. The collected data were analyzed by comparing pre- and post-test results to measure the program’s effectiveness. The findings revealed a significant improvement in the participants’ social skills, allowing them to interact more effectively with their surroundings and reintegrate into their family environments following a reduction in the severity of their symptoms. Some initial resistance to therapy was observed due to auditory and visual hallucinations, but these diminished after three to four sessions. The study confirmed the effectiveness of psychoeducational therapy in improving social skills among individuals with schizophrenia, contributing to their reintegration and reducing relapse risks. Furthermore, it underscored the need to expand Arabic research in this field to develop more effective therapeutic interventions.